A Novel Titanium Cranioplasty Technique of Marking the Coronal and Squamosoparietal Sutures in Three-Dimensional Titanium Mesh as Anatomical Positioning Markers to Increase the Surgical Accuracy and Reduce Postoperative Complications - Xie, Bing-Sen; Wang, Fang-Yu; Zheng, Shu-Fa; Lin, Yuan-Xiang; Kang, De-Zhi; Fang, Wen-Hua (Frontiers in Surgery, 2021)
Objective: To modify titanium cranioplasty (Ti-CP) technique to increase the surgical accuracy and preliminarily verify the effectiveness and safety of this improvement. Methods: We developed a novel technique of marking the coronal and squamosoparietal sutures in three-dimensional (3D) titanium mesh as anatomical positioning markers, and designed a prospective trial in patients with a unilateral frontotemporoparietal skull defect. Patients were randomly divided into two groups by the presence or absence of the anatomical positioning markers, and the therapeutic effects of these two groups were compared. Results: Forty-four patients were included in this study, including 28(64%) males and 16(36%) females. The mean age was 44.8±15.2 years (range, 13-75 years). Overall postoperative complication rate of the intervention group (18%) was significantly (P=0.03) lower than the control group (50%). Surgical accuracy of the intervention group (97.8%) was significantly (P<0.001) higher than the control group (94.0%). Visual analog scale for cosmesis (VASC) of the intervention group (8.4) was significantly (P<0.001) higher than the control group (7.0). The overall postoperative complication rate was 34%. Multivariate analyses showed that surgical accuracy<95.8% (OR=19.20, 95% CI=3.17-116.45, P=0.001) was significantly associated with overall postoperative complications. Independent predictor of overall postoperative complications was surgical accuracy (OR=0.57, 95% CI=0.40-0.82, P=0.002). Conclusions: This novel technique for repairing frontotemporoparietal skull defects increases surgical accuracy, improves cosmetic prognosis and reduces postoperative complications. Therefore, it is a safe and effective improvement for Ti-CP.